Design and motion analysis of a small motor stator multi-wire paralleled winding hybrid robot - Y. Zhao (Copernicus Publications, 2021)
The working space of small motor stators is narrow, and most of them are manual winding. It is difficult to guarantee the uniform arrangement of enameled wires by multi-wire winding. To solve these problems, a three-phase parallel equivalent multi-wire winding robot is proposed to achieve large output torque of the motor. Firstly, according to the equivalent model, the structure of the large arm, small arm and manipulator is designed to determine the motion model of the winding robot. Euler's kinematics theory is used to analyze the change of the working position of the arm, and the rotation matrix of the arm and the constraint equation of the motion vector of each branch chain are established. The motion model of the arm and the manipulator are established using inverse kinematics and analytical analysis. The motion pose of each joint of the winding robot is studied to ensure that the robot realizes a three-phase parallel multi-wire winding motion. ADAMS software was used for kinematic simulation analysis of the winding robot. The displacement of the branch chain on the xyz axis was represented by the torque of the virtual motor to verify the correctness of the inverse kinematics solution and the closure condition of the manipulator block. Finally, the ROS simulation platform is built to simulate the joint motion planning of the winding robot to verify the multi-line parallel principle and the feasibility of the multi-line parallel winding hybrid robot. The research results of this paper provide a theoretical reference for multi-wire parallel winding equipment control.